Unveiling Consumer Affection: Exploring the Psychological Forces Driving Love and Willingness to Pay for Premium Laptop Brands - Nofrizal Nofrizal; Arizal N; Aznuriyandi Aznuriyandi; Nurhayani Lubis; Mohammad Tahir Zainuddin (Media Ekonomi dan Manajemen, 2024)
Premium laptop brands are increasingly loved by consumers, and despite the high prices, they are still willingness to pay. This study aims to determine the driving factors of consumer brand love and willingness to pay for premium laptop products. Psychological factors such as social status, Fear of Missing Out (FOMO), and Hedonism are driving factors. The survey technique was used to collect data on the answers of premium laptop consumer respondents using purposive sampling of 633 buyers of premium laptop products. Data analysis of data processing and presentation using Structural Equation Modeling using SmartPLS 4.0 software. The results showed that social status and Hedonism are driving factors for brand love and willingness to pay for premium laptop products. Next, FOMO feelings also cause hedonism, but cannot make customers willingness to pay (WTP). The role of brand love and hedonism can mediate social status and FOMO on willingness to pay.